Investigations on mechanical behavior of AA2014-T6 weldments developed using CMT welding: As-weld and post weld heat treatment conditions - Balram Yelamasetti; B Tulasi Lakshmi Devi; N Santhi Sree; Sai Vempati; Tushar Sonar; Ashish Kumar; C. Rakesh; Ankit Sharma; Mushtaq Ahmad Ansari (Journal of Materials Research and Technology)
This research work aims to investigate the tensile properties, micro-hardness and microstructural changes of AA2014-T6 cold metal transfer (CMT) weldments in as-weld and post-weld heat treatment (PWHT) conditions. X-ray radiography test is conducted to inspect the internal defects and confirmed that the welded structures were free from macro/micro defects. The welded structures are tested to evaluate the tensile properties, micro-hardness and microstructural changes in both the conditions. The ultimate tensile strength (UTS) of CMT1 and CMT2 is observed as 316 and 241 MPa, respectively in as-weld condition whereas the UTS value of CMT1 & CMT2 is 376 and 325 MPa, respectively after heat treatment. The welding strength is improved by 18.9 and 34.8% in CMT1 & CMT2 respectively when the samples were subjected to heat treatment process. The average hardness value of 105 and 106 HV is observed in CMT1 & CMT2, respectively in as-weld condition. Whereas, the hardness number is increased to 128 and 121 HV in CMT1 & CMT2, respectively when the samples were subjected to heat-treatment. After PWHT, the weld zone is more homogeneous than when it was first welded, indicating that PWHT has been effective in reducing thermal stresses and promoting the formation of a more homogeneous microstructure.